The Study on Hybridized Two-Band Superconductor - T. Chanpoom; J. Seechumsang; S. Chantrapakajee; P. Udomsamuthirun (Advances in Condensed Matter Physics)
The two-band hybridized superconductor which the pairing occurred by conduction electron band and other-electron band are considered within a mean-field approximation. The critical temperature, zero-temperature order parameter, gap-to-Tc ratio, and isotope effect coefficient are derived. We find that the hybridization coefficient shows a little effect on the superconductor that conduction electron band has the same energy as other-electron band but shows more effect on the superconductor that conduction electron band coexists with lower-energy other-electron band. The critical temperature is decreased as the hybridization coefficient increases. The higher value of hybridization coefficient, lower value of gap-to-Tc ratio, and higher value of isotope effect coefficient are found.